Didaktické inspirace k aktivizační výuce ve středoškolském dějepisu - Fasora, Lukáš (Masaryk University Press, 2023)
Title in English: Didactic inspirations for activation teaching in secondary school history The publication serves as a support for secondary school teachers for the development of activation teaching in history.